If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1)(2x + 1) = 0 Reorder the terms: (-1 + x)(2x + 1) = 0 Reorder the terms: (-1 + x)(1 + 2x) = 0 Multiply (-1 + x) * (1 + 2x) (-1(1 + 2x) + x(1 + 2x)) = 0 ((1 * -1 + 2x * -1) + x(1 + 2x)) = 0 ((-1 + -2x) + x(1 + 2x)) = 0 (-1 + -2x + (1 * x + 2x * x)) = 0 (-1 + -2x + (1x + 2x2)) = 0 Combine like terms: -2x + 1x = -1x (-1 + -1x + 2x2) = 0 Solving -1 + -1x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -2x)(1 + -1x) = 0Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-0.5, 1}
| 320=24+20 | | x^2+28x+5=0 | | y^2+16y+28=0 | | 6x^2-9-13x^2+11+11x= | | 3p+3=14 | | 12+(34-5)= | | 3(x+8)=15 | | -16x=-48 | | 5x^2-5=0 | | x-3x=8 | | 8x-9=7x-3 | | 9.4m= | | 0.5(3x+2)-0.2(x+6)=5 | | 0.33(2x+3)-0.2(x+6)=4 | | 3(n-9)=30 | | 12(x+3)=3(4x+5)+21 | | 3x^4=16x^2+12 | | 0.5(x+2)=0.25(2x+4) | | 0.2(4x+7)=3(4-4x)+15 | | 14m-2=2(8m-5) | | -5x+4= | | 21x=9x^4+6x^2+1 | | -0.16(x-18)+3(x+3)=x-6 | | 400=21x | | 9x+4=2(4x-2)+8 | | 3x^2=52x | | 4m^2n+5m^2p-4mnp= | | -3+9(x-1)=16x+4-7x | | 30x+25+-3x-3=30x-15 | | 6v-9=3(v-6) | | 9(u-6)=-7u-22 | | 7w-48=-3(w-4) |